The effect of acute branched-chain amino acids ingestion on rate of force development in different time intervals: a controlled crossover study - Zhang, Xi-Nuan; Li, Long-Ji; Tu, Yan-Hao; Zhang, Li-Feng; Shang, Hua-Yu; Liu, Meng; Li, Ming-Da (Frontiers in Nutrition, 2025)
BackgroundBranched-chain amino acids (BCAAs) are widely used as sports nutrition supplements. However, their impact on the rate of force development (RFD), an indicator of explosive muscle strength, has not yet been validated. This study aimed to assess the impact of BCAA supplementation on the RFD in college basketball players during simulated games.MethodsThis study employed a randomized, controlled crossover, double-blind design. Participants received either BCAAs (0.17 g/kg combined with 0.17 g/kg isocaloric glucose) or a placebo (0.34 g/kg isocaloric glucose) orally 30 min before beginning the exercise protocol. The RFD was quantified using the isometric mid-thigh pull (IMTP) test. Additional outcome measures, including strength and jump tests, agility and sprinting tests, and physiological responses, were also assessed. A two-way repeated measures ANOVA was employed to evaluate the impact of supplements (BCAAs and placebo) on RFD and other related outcome measures.ResultsAnalysis of the 50 ms RFD demonstrated significant main effects of BCAA supplementation (p = 0.003). The BCAAs group consistently exhibited higher levels of 50 ms RFD compared to the placebo group across rounds 1 to 4. For example, in round 1, the 50 ms RFD was 3702.3 ± 1223.2 N/S in the BCAAs group versus 2931.3 ± 888.8 N/S in the placebo group (p = 0.045). Although no significant between-group differences were observed for the 100, 150, 200, and 250 ms RFD measurements, the BCAAs group consistently showed superior values across all time points. The results of other outcome indicators also suggested that supplementation with BCAAs was indeed effective.ConclusionThe results indicate that BCAA supplementation can enhance RFD in basketball players, particularly at the 50 ms RFD. Our research design provides reliable insights into the effects of BCAAs on athletic performance. Further studies of similar design with larger sample sizes are necessary to confirm and extend these findings.Clinical trial registrationChinese Clinical Trial Registry, ChiCTR2400091314 (https://www.chictr.org.cn).